VD_FINDINFO HC / 2013 / 180 vom 18. Januar 2013 - VD Tribunal cantonal (2013)
MOTIF DE RÉVISION, RÉVISIONDÉCISION, ASSISTANCE JUDICIAIRE | 122 al. 1 let. d CPC (CH), 328 al. 1 let. a CPC (CH), 332 CPC (CH), 59 CPC (CH), 60 CPC (CH)